IMPLEMENTASI MASTER PLAN KEGIATAN SERAYU RIVER VOYAGE (SRV) DALAM RANGKA PENGEMBANGAN PARIWISATA DI KABUPATEN BANYUMAS (Studi Di Dinas Pemuda Olahraga Kebudayaan dan Pariwisata Kabupaten Banyumas) - Imam Pamungkas; Agus Suryono; Sarwono Sarwono (Pro Bisnis, 2015)
The background of research is that Master Plan Activity Serayu River Voyage (SRV) that compiled by department of tourism and culture Banyumas Regency in 2007 but the implementation has not been in line with expectations and stagnation. That Master Plan Activity Serayu River Voyage (SRV) expected completed within five years from 2008 to 2012, but during the period until 2013 programs and activities in the Master Plan Activity Serayu River Voyage (SRV) most have not been implemented. The results showed that the Master Plan of Activities Serayu River Voyage (SRV) in the Framework of Tourism Development in Banyumas Regency has not been implemented properly the cause is is the absence of good coordination between agencies, the lack of integration of programs and activities (overlap), supporting documents have not been revised, no good socialization, and the role of the private sector is still lacking. The actors that constrain and support implementation of the Master Plan Activity Serayu River Voyage (SRV) is supporting factors : competent human resources (implementor) already available at the managerial level and who have intellectual tourism, only need to be added to personnel in the field of culture , pamong budaya. The availability of adequate budget. Institutions that have been effective and efficient. High community response. High commitment of Regent Banyumas and cooperation related parties (stakeholders). Natural conditions Serayu tend to calm the river slope condition ( i ) is small. The constrain factors: regulatory policies, integration of programs and activities, Coordination and socialization that occurs sectoral ego that it is time to be addressed